Pemberdayaan Kader Nagari untuk Mencegah Tindakan Bunuh Diri di Kabupaten Tanah Datar - Wahyu Pramono; Indraddin Indraddinti; Aziwarti Aziwarti; Dwiyanti Dwiyanti (Jurnal Pengabdian Warta Andalas, 2018)
Precaution against the act of suicide not only a responsibility government officials but must be shared responsibility all members of the community. How empower communitymembers to prevent the act of suicide in by teenagers? Problems solutions by using the methodinformation about the phenomenon suicide and factors encourages young people do kill as wellas the cause preceded it; formulate with an appropriate way in preventing the act of suicide.The role of kaders in resolving the conflict suicides among teenagers very important. A rolethat can be run by kader is as an adviser, motivator for the teenager who was desperate, anddiseminator various knowledge and how to resolve the problems faced by teenagers andfacilitators activities test to fill leisure teenagers. Make kader can act independent in dealingwith the youth in their environment is very important for handling the suicide are visible notopen detectable since the beginning.The various need to get knowledge to run the role of themotivator and advisor for youth who trouble.